PENGARUH PENGGUNAAN MEDIA AUGMENTED REALITY TERHADAP KETERAMPILAN MENYIMAK SISWA SEKOLAH DASAR KOTA MAKASSAR - Salam, Rosdiah; Suryani Sahabuddin, Erma; Magfira, Magfira (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2024)
This study discusses the effect of using augmented reality media on students' listening skills at UPT SPF SD Inpres Layang Tua II Makassar City which aims to determine the description of the use of augmented reality media for students, to determine the description of listening skills of class students, to determine the effect of using augmented reality media on students' listening skills. The approach used in this research is a quantitative approach with the type of One Group Pretest-Posttest Design. The population in this study were class V UPT SPF SD Inpres Layng Tua II students, the sample was 19 students selected using saturated sampling technique. Data collection techniques using observation and tests. The data analysis techniques used were descriptive statistical analysis and inferential analysis. The results showed that the description of the use of augmented reality media was carried out in a good category, the description of the results of the student listening skills test showed a significant difference in students' listening skills with an increase from the average petest score in the incomplete category while the posttest score was in the complete category, and there was an effect of using augmented reality media on listening skills of class V UPT SPF SD Inpres Layang Tua II students as evidenced by hypothesis testing using the t-Test formula assisted by IBM SPSS Statistic.